Two-dimensional silver nanonetwork on Ag4Ti5O12 film as highly efficient SERS substrate - Qamar U.; Hazra S.; Kant C.; Uday Ghosh U.; Nath Pal B.; Das S. (My University, 2025)
Surface Enhanced Raman Spectroscopy (SERS) is a powerful technique to study and detect single molecules adsorbed onto a surface. In this work, molar concentrations were varied over three consecutive orders of magnitude (10-3 M, 10-6 M, 10-9 M) of Methylene Blue (MB) to study SERS on different thicknesses of silver (6, 8, 10, 12 nm) coated on Ag4Ti5O12 deposited onto glass substrates as the base material. The Ag4Ti5O12 thin films were prepared by a unique ion-exchange method where Li4Ti5O12 thin films were initially deposited by the sol–gel method followed by the exchange of Li+ ion with Ag+ ion. The varied thicknesses of thermally deposited Ag-thin films were grown with unaltered Ag+ ions nucleation sites atop the Ag4Ti5O12 layer to create the two-dimensional (2D) nanonetwork. The structure and morphology of the as-prepared thin-film samples were characterized using X-ray diffraction, Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM) techniques. The SERS enhancement factor (EF), calculated using Raman spectroscopy, showed the systematic changes in the Raman signal enhancement as a function of Ag-thickness. The 10 nm thick as-deposited Ag sample showed the highest signal enhancement in Raman spectra than the other Ag thickness films. The successive signal enhancement was obtained due to forming the critical nuclei size of Ag on top of Ag4Ti5O12, which was further endorsed with film surface roughness and surface energy measurements. The as-prepared Ag-10 nm sample showed the lowest film roughness of ∼2.07 nm, in tune with the maximum enhancement factor (EF). We believe this work could open wide opportunities for developing efficient SERS substrates with sensing capabilities for ultra-low analyte concentration coupled with low cost and high enhancement factors. © 2023 Elsevier B.V.